-p-4+6p=3p+9+2p-13

Simple and best practice solution for -p-4+6p=3p+9+2p-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -p-4+6p=3p+9+2p-13 equation:


Simplifying
-1p + -4 + 6p = 3p + 9 + 2p + -13

Reorder the terms:
-4 + -1p + 6p = 3p + 9 + 2p + -13

Combine like terms: -1p + 6p = 5p
-4 + 5p = 3p + 9 + 2p + -13

Reorder the terms:
-4 + 5p = 9 + -13 + 3p + 2p

Combine like terms: 9 + -13 = -4
-4 + 5p = -4 + 3p + 2p

Combine like terms: 3p + 2p = 5p
-4 + 5p = -4 + 5p

Add '4' to each side of the equation.
-4 + 4 + 5p = -4 + 4 + 5p

Combine like terms: -4 + 4 = 0
0 + 5p = -4 + 4 + 5p
5p = -4 + 4 + 5p

Combine like terms: -4 + 4 = 0
5p = 0 + 5p
5p = 5p

Add '-5p' to each side of the equation.
5p + -5p = 5p + -5p

Combine like terms: 5p + -5p = 0
0 = 5p + -5p

Combine like terms: 5p + -5p = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 9X^5-12X=0 | | 16x-3+11x+2=180 | | Differentiate:(cos2x)^1/2 | | (11x+22)(2x-18)= | | -5x-9=3x+y | | k-8k=0 | | -5+-x= | | 100=5x-2y+85 | | 9x+30=4x+105 | | y=(x-5i)(x+5i) | | 18x=-100-2x | | 75/c=15/8 | | 10z+9=2 | | 3x-3/x-1=2x/x | | (x*2)+(y*4)=99 | | 7.15x+16=51.1225+4x | | y=0.15x+49 | | 35=(f-32)5/9) | | 8z+2=10 | | -2-x=15 | | log(19)=0.471 | | 14.5x=19.5y | | x=6/x-1 | | x-y=117 | | W+1.6=13 | | log(19)4=0 | | (3x^3+3x^2+4x+7)+(5x^3+2x^2+x+9)= | | 7.5h=3.2 | | 7.8a+15=100.8 | | sqrt(4x+9)-8=5 | | 1/5d=72 | | 3x+2=-x-6 |

Equations solver categories